Gastroprotective effects of Corchorus olitorius leaf extract against ethanol‐induced gastric mucosal hemorrhagic lesions in rats. Issue 8 (22nd July 2013) - Al Batran, Rami; Al‐Bayaty, Fouad; Ameen Abdulla, Mahmood; Jamil Al‐Obaidi, Mazen M; Hajrezaei, Maryam; Hassandarvish, Pouya; Fouad, Mustafa; Golbabapour, Shahram; Talaee, Samaneh
Abstract Background and Aim Corchorus olitorius is a medicinal plant traditionally utilized as an antifertility, anti‐convulsive, and purgative agent. This study aimed to evaluate the gastroprotective effect of an ethanolic extract of C. olitorius against ethanol‐induced gastric ulcers in adult Sprague Dawley rats. Methods The rats were divided into seven groups according to their pretreatment: an untreated control group, an ulcer control group, a reference control group (20 mg/kg omeprazole), and four experimental groups (50, 100, 200, or 400 mg/kg of extract). Carboxymethyl cellulose was the vehicle for the agents. Prior to the induction of gastric ulcers with absolute ethanol, the rats in each group were pretreated orally. An hour later, the rats were sacrificed, and gastric tissues were collected to evaluate the ulcers and to measure enzymatic activity. The tissues were subjected to histological and immunohistochemical evaluations. Results Compared with the extensive mucosal damage in the ulcer control group, gross evaluation revealed a marked protection of the gastric mucosa in the experimental groups, with significantly preserved gastric wall mucus. In these groups, superoxide dismutase and malondialdehyde levels were significantly increased (P < 0.05) and reduced (P < 0.05), respectively. In addition to the histologic analyses (HE and periodic acid‐Schiff staining), immunohistochemistry confirmed the protection through the upregulation of Hsp70 and the downregulation of Bax proteins. The gastroprotection of the experimental groups was comparable to that of the reference control medicine omeprazole. Conclusions Our study reports the gastroprotective property of an ethanolic extract of C. olitorius against ethanol‐induced gastric mucosal hemorrhagic lesions in rats.